TRANSFORMATIONS OF FAMILY STRUCTURES: PERCEPTION OF NEW FAMILY MODELS IN THE REPUBLIC OF NORTH MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2020)
Historical and demographic processes have significantly influenced the transformationfrom traditional to modern family, changing its structure, functions, partnerships,as well as parenting and child rearing, perceptions of marriage, divorce,birth-rates, etc. After the Industrial revolution, the nuclear family became the dominantmodel of family in Europe and it is still prevailing in the Macedonian contemporarysociety.Social changes such as globalization, individualization, secularization, and thedynamics of modern living have led to new family forms that reflect modern societies.This paper will present a brief analysis of family structures, the transformation fromtraditional to modern family and it will discuss new family models. Particularly, it willfocus on cohabitation, multi-ethnic families and same-sex relationships in the Republicof North Macedonia by presenting the results of a qualitative research on perception ofnew family models in North Macedonia conducted during 2019.
Keywords: FAMILY MODELS; COHABITATION; MULTI-ETHNIC FAMILIES; SAME-SEX RELATIONSHIPS; MACEDONIA